Osnove projektiranja konstrukcij - Premrov, Miroslav; Kozem Šilih, Erika (University of Maribor Press, 2017)
Basics of Structural Design. The textbook "Basics of Structural Design" is intended as a basic material and help for undergraduate study in the field of structural design. In the textbook there are given all the important facts in the topics of design, analysis of actions on structures and earthquake engineering, which are the basis for understanding the behavior of building structures. The content of the textbook relates to the requirements of the following European standards: Eurocode: Basics of structural design, Eurocode 1: Actions on structures – Part:1.1: General actions - Densities, self-weight and imposed loads of buildings , Eurocode 1: Actions on structures – Part: 1.3: General actions - Snow loads, Eurocode 1: Actions on structures – Part: 1.4: General actions - Wind actions and Eurocode 8: Design of structures for earthquake resistance - Part 1: General rules, seismic actions and rules for buildings.